Modules of elasticity and rupture of laminated wood of three tropical species - Sotomayor Castellanos, Javier Ramón; Adachi, Koji; Ryuichi, Iida; Hayashi, Tomoyuki (Acta Universitaria, 2019)
The correct use of laminated beams requires that their mechanical strength be characterized. The objective of the research was to determine the density, the modulus of elasticity and the modulus of rupture in small sized specimens of solid and laminated wood of Enterolobium cyclocarpum, Tabebuia rosea and Jouglas pyriformis. It is concluded that laminated wood, made with wood of the same species, increases its density. But, for the case of the modulus of elasticity and rupture, they increase or decrease depending on the species and/or depending on whether the wood is solid or laminated. The results of the bending tests suggest that the magnitude of the modulus of elasticity and the modulus of rupture are similar to those reported in the literature for solid and laminated wood, manufactured with vinyl polyacetate adhesives.